Edukasi Pendampingan Administrasi Sertifikasi Halal dan Nomor Induk Berusaha dalam Mendukung Daya Saing UMKM Desa Pakel, Bareng, Kabupaten Jombang - Muhammad Iqbal; Regita Ayudhea Permata Putri; Nailatun Ni’mah; Mu’tasim Billah; Ika Lestari; Sinta Nur Aini (STIPAS Tahasak Danum Pambelum Keuskupan Palangkaraya, 2023)
The government promotes the obligation to own business legality as controlling economic activity in the development of Micro, Small and Medium Enterprises (MSMEs). Business legality as the ownership identity of a legally operating business entity. Pakel Village, Bareng District, Jombang Regency, has various types of MSMEs that excel in agro-industry. However, the issue of business legality is still an obstacle to the progress of the Pakel Village MSMEs, namely the uneven ownership of business legality such as Business Permit Numbers (NIB), Home Industry Product Permits (PIRT), halal certification and so on. Pakel Village UMKM actors lack knowledge and awareness of the importance of business legality, starting from the requirements to the submission mechanism, the administrative process is considered complicated and time-consuming, and the management costs are expensive. The purpose of this community service activity is for Pakel Village MSMEs to know and understand how to make NIB independently through the Online Single Submission (OSS) application and assistance in submitting halal certification for free through SiHalal with the Sehati 2023 program using the business actor's statement mechanism. The method of implementing the KKNT 09 Desa Pakel group in this community service activity is to conduct socialization and mentoring on the importance of NIB ownership and halal certification with MSME Facilitators from the Ministry of Religion, Jombang Regency. The result of this community service activity is the issuance of NIB and halal certification for Pakel Village MSMEs